Fused Deposition Modeling of Polyolefins: Challenges and Opportunities. Issue 1 (25th October 2022) - Verma, Nandishwar; Awasthi, Pratiksha; Gupta, Akash; Banerjee, Shib Shankar
Abstract: Polyolefins are the largest class of commercially available synthetic polymers that are extensively used in a variety of applications from commodities to engineering owing to their low cost of production, good physico‐mechanical properties, light weight, good processability, and recyclability. Compared to conventional molding techniques, fused deposition modeling (FDM)‐based 3D printing is a smart manufacturing technology for thermoplastics due to its low cost, ease of production of complex geometrical parts, rapid prototyping, and scalable customization. FDM 3D printing can be an ideal manufacturing technology for polyolefins to manufacture various complex parts. However, FDM 3D‐printing of polyolefins is challenged bycritical printing problems like high warpage, dimensional inaccuracies, poor bed adhesion, and poor layer‐to‐layer adhesion. In this review, a fundamental understanding of polyolefins and their FDM 3D‐printing process is established, and the recent progress of FDM 3D printing of polyolefins is summarized. Furthermore, strategies to overcome warpage and to improve mechanical strength of the 3D‐printed polyolefins are provided. Finally, future prospectives of FDM 3D‐printing of polyolefins are critically discussed to inspire prospective research in this field. It is believed that this review article can be tremendously useful for research work related to FDM of polyolefin‐based materials. Abstract : This review provides a fundamental understanding of polyolefins and their fused deposition modeling 3D‐printing process. The recent progresses in 3D‐printing of polyolefins are summarized. Importantly, strategies to overcome the warpage of polyolefins during the 3D‐printing process, and future prospective to inspire potential research in this area are provided.